2007
DOI: 10.1111/j.1365-2222.2007.02847.x
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for asthma at 3.5 and 7 years of age

Abstract: There was a significant association between antibiotic use and day care in the first year of life and wheezing at 7 y but not at 3.5 y. This strengthens the argument that these factors increase the risk of asthma. We have also made the novel observation that sleeping on a used mattress in the first year of life is a risk factor for wheezing at 3.5 and 7 y. Capsule summary This prospective study of 871 children made the novel observation that sleeping on a used mattress in the first year of life was a risk fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 52 publications
0
13
1
Order By: Relevance
“…There were six dissenting studies [4145], and with respect to one of these, the authors reached the opposite conclusion on a later occasion [46]. Moreover, Mitchell et al [47], while seeing the case for an antibiotic causation strengthened, acknowledged the possibility of confounding by indication. The authors of the remaining study [48] considered both bias and true causation possible, but suggested confounding by indication in a later overview [66].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There were six dissenting studies [4145], and with respect to one of these, the authors reached the opposite conclusion on a later occasion [46]. Moreover, Mitchell et al [47], while seeing the case for an antibiotic causation strengthened, acknowledged the possibility of confounding by indication. The authors of the remaining study [48] considered both bias and true causation possible, but suggested confounding by indication in a later overview [66].…”
Section: Discussionmentioning
confidence: 99%
“…2) Causal association concluded Prospective Birth Cohort Studies (Cases of interest identified after recruitment)Alm et al [41] (studied age group (until 12 months) does not allow firm conclusions on asthma; no adjustment for respiratory infections, confounding by indication still possible); Risnes et al [42] (interview 6 years after birth, recall bias possible); Goksör et al [43] (broad spectrum antibiotics were considered causative, no details; confounding by indication possible due to lack of information on infectious diagnosis); Jedrychowski et al [44] (when adjusted for respiratory infections, the Odds ratio lost statistical significance; macrolide and cephalosporin associations lost strength, but retained significance; considered that immuno-modulation might underlie asthma promotion by (certain) antibiotics); Marra et al [45] (after excluding children with upper or lower respiratory infection the hazard ratio still showed a small association between antibiotics and asthma (but cf. Marra et al [46], below)); Causal association as well as confounding by indication considered Mitchell et al [47] (no adjustment for airway infections; concluded that antibiotics are a risk factor but considered confounding by respiratory infections); Kummeling et al [48] (no adjustment for airway infections; in a later overview, the same authors suggested confounding by indication (Kummeling and Thijs [66])) Association explained by confounding factors or no associations found Marra et al [46] (considered that antibiotics were used for asthmatic wheeze (reverse causation)); Kusel et al [49] (concluded that the data did not indicate that using antibiotics early in life led to asthma at 5 years; cf. Fig.…”
Section: Factors That Might Set the Stage For Asthma Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…15 studies were excluded for the following reasons: antibiotic exposure was collected retrospectively (n54) [9][10][11][12]; no report on wheeze and/or asthma, but other allergic outcomes only (n56) [13][14][15][16][17][18]; no association measure for wheeze or asthma separately but an overall outcome called ''atopy'' which also included eczema and/or hay fever (n51) [19]; only prenatal antibiotic use reported (n53) [20][21][22]; and adult population (n51) [23].…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
“…Therefore, this study will only be discussed in the following section, together with the remaining eight studies in which the positive association could not be explained by RC. [29] FOLIAKI [24] Ecological design SARIACHVILI [17] JOHNSON [16] VOOR [18] BREMNER [13] BREMNER [14] EGGESBO [15] FAROOQI [19] MITCHELL [10] THOMSEN [11] AWASTHI [9] WJST [12] JEDRYCHOWSKI [21] McKEEVER [22] BENN [20] CULLINAN [23] FIGURE 1. Results of the literature search and selection of studies.…”
Section: Reverse Causationmentioning
confidence: 99%